(untitled) (GEOmedia, 2010)
The italian geological service Geoportal On may 25th, ISPRA, Institute for Environment Protection and Research, presented the Web Service for the new portal of Geologic Survey of Italy. Through simple tools it allows to search and examine documentation and databases owned by Italian Geologic Survey. It consists in two different levels: the first one is a searchable repository of metadata of databases stored within SGI-ISPRA and from external web services and the latter is a WebGIS interface that shows geological, geophysical and other environmental data surveyed and produced at different scales. All metadata are compliant with ISO 19119 and 19115 standards. INSPIRE and OGC compliant web services WMS, WCS and WFS are available as well as other formats like ESRIArcGIS and KML /KMZ